Antecedents of moral disengagement: Preliminary empirical study in Malaysia - Saidon, I.; Galbreath, Jeremy; Whiteley, Alma (ANZAM, 2010)
This study, conducted in Malaysia is part of the pilot study carried out as a pre-test procedure to a main study on moral disengagement. According to social cognitive theory, moral disengagement is the key to deactivate individual self- regulatory process. Once it is deactivated an individual will be freed from any psychological feeling of discomfort in performing unethical behaviour. Hence, based on social cognitive theory this study aims to identify the antecedents of moral disengagement by investigating the individual differences (gender and personality) and environmental influence (organizational ethical climate). ANCOVA and hierarchical regression were applied to test the hypotheses. There was a moderate gender difference in the level of moral disengagement between male and female employees. As predicted, conscientiousness and extraversion were found to have a negative significant relationship with moral disengagement. Further, organizational ethical climate was found to be negatively and modestly related to moral disengagement.